Temporal Trends and Meteorological Associations of Particulate Matter and Gaseous Air Pollutants in Tehran, Iran (2017–2021) - Fatemeh Yousefian; Zohreh Afzali Borujeni; Fatemeh Akbarzadeh; Gholamreza Mostafaii (Atmosphere)
Air pollution is a major environmental risk factor that contributes significantly to the global burden of disease, particularly through its impact on respiratory and cardiovascular health. The aim of this study is to investigate the temporal variations of ambient air pollutants and the influence of MPs (MPs) on their concentrations in the metropolitan area of Tehran from 2017 to 2021. Hourly data for PM2.5, PM10, O3, NO2, SO2, and CO from all air quality monitoring stations were obtained. Effects of MPs for the same period were assessed. The results revealed that Tehran’s residents are continuously exposed to harmful levels of PM2.5 (5.7 to 6.3 times), PM10 (4.5–5.6 times), and NO2 (8.7–10.0 times) that are significantly higher than the updated World Health Organization (WHO) air quality guidelines. All other air pollutants (except for O3) showed the lowest and highest concentrations during summer and winter, respectively. The highest concentration of O3 was found on weekends (weekend effect), while other ambient air pollutants had higher levels on weekdays (holiday effect). Although other air pollutants exhibited two peaks, in the morning and late evening, the hourly concentration of O3 reached its maximum level at 3:00 pm. Approximately 51% to 65% of the Air Quality Index (AQI) values were classified as unhealthy for sensitive groups. Throughout the study period, PM2.5 was identified as the primary pollutant affecting air quality in Tehran. Among MPs, temperature was the most important factor in increasing the concentration of O3, while the other ambient pollutants decreased under the influence of wind speed. Given the current situation, effective and evidence-based air quality management strategies, like those that have been successfully applied elsewhere, are now a necessity to avoid the public health impact and economic losses from air pollution. Although this research focuses on Tehran as a model case of rapidly developing cities facing severe air quality challenges, the findings and recommendations have broader applicability to similar urban environments worldwide.